1993
DOI: 10.1111/j.1365-2672.1993.tb02798.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of vitamins by pure cultures of tempe moulds and bacteria during the tempe solid substrate fermentation

Abstract: The formation of water soluble vitamins (vitamin B12, vitamin B6, riboflavin, thiamine, nicotinic acid and nicotinamide) during the tempe solid substrate fermentation was investigated. The role of several strains of Rhizopus oligosporus, R. arrhizus, and R. stolonifer and the role of several bacteria in the vitamin formation process were checked. All fungal and bacterial strains were isolated from Indonesian tempe and soaking water samples. The Rhizopus strains formed riboflavin, nicotinic acid, nicotinamide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 13 publications
1
47
1
Order By: Relevance
“…Tempe is good for health because it contains essential compounds such as isoflavone (Ikehata et al 1968) and vitamin B12 (Keuth & Bisping 1993;Wiesel et al 1997). Liem et al (1977) reported that Indonesian tempe, a proteinrich vegetarian food, is one of the world's first meat analogs.…”
Section: Introductionmentioning
confidence: 98%
“…Tempe is good for health because it contains essential compounds such as isoflavone (Ikehata et al 1968) and vitamin B12 (Keuth & Bisping 1993;Wiesel et al 1997). Liem et al (1977) reported that Indonesian tempe, a proteinrich vegetarian food, is one of the world's first meat analogs.…”
Section: Introductionmentioning
confidence: 98%
“…An example of the fungal stimulation of a bacterial product can be seen in the enhancement of nisin (a food preservative) biosynthesis by Lactococcus lactis upon cocultivation with yeast that is able to metabolize inhibitory lactic acid that is produced during the fermentation (222). An understanding of neutral BFIs may also be of benefit in some circumstances; for example, the selection of vitamin-producing bacterial strains that can be cocultured with Rhizopus was suggested as a method for the provision of vitamin B 12 in tempeh production (190,405).…”
Section: Natural Product Discovery and Synthetic Biologymentioning
confidence: 99%
“…Murata et al (1967) reported increases of riboflavin from 8-to 47-fold, pyridoxine from 4-to 14-fold, and niacin from 2-to 5-fold in tempes manufactured and sun-dried in Indonesia. Keuth and Bisping (1993) studied the production of vitamins by pure cultures of tempe molds and bacteria during the tempe solid substrate fermentation. Rhizopus oligosporus, R. arrhizus and R. stolonifer produced riboflavin, nicotinic acid, nicotinamide and pyridoxine (vitamin B6)' R. oligosporus was the best vitamin producer.…”
Section: Indonesian Tempementioning
confidence: 99%